Simplified Azbel model to adjust Peruvian mortality tables for pension purposes - Infante Rojas, Magen Danielle (2023)
In this research, the Simplified Azbel model was estimated to verify that it is a good fit to mortality rates for pension purposes in Peru, using three estimation methods, maximum likelihood (MV), log-linear regression-type method and ordinary least squares (OLS) method. The mortality tables were segmented into three age groups. It was confirmed that there is a difference in the fit between men and women. With the A/E and ARL similarity metrics, the original and the estimated mortality tables, the hypothesis is corroborated since it is concluded that the best estimates resulted for the SP2005 tables, for the male gender with the Log-linear Regression-type and ordinary least squares methods, except for the range between 50 and 90 years of age. In women, there is only a good fit with the Log-linear Regression-type method from 15 years of age onwards. The fit to the SPP2017 tables is barely noticeable in men with the Log-linear Regression-type method from the age of 70 years and in women from the age of 80 years.